1995
DOI: 10.1007/bf00402175
|View full text |Cite
|
Sign up to set email alerts
|

Candidate gene studies in pedigrees with maturity-onset diabetes of the young not linked with glucokinase

Abstract: Maturity-onset diabetes of the young (MODY) is a form of non-insulin-dependent diabetes mellitus characterised by an early age of onset and an autosomal dominant mode of inheritance. Only a proportion of cases are due to mutations in the glucokinase gene. We have studied five Caucasian MODY families, including the first MODY family to be described, with five candidate genes implicated in regulation of insulin secretion. The affected subjects showed more marked hyperglycaemia than that found in subjects with gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…Glucokinase is essential for glucose metabolism in the ␤ cell; some mutations in the glucokinase gene reduce the affinity of the enzyme for glucose resulting in a small increase in the plasma glucose concentrations (11). While this subtype accounts for 60% of MODY in France (12), it is less prevalent elsewhere (13,14). Recently, MODY3 was identified by linkage to a region on the long arm of chromosome 12 (15).…”
Section: Non-insulin-dependent Diabetes Mellitus (Niddm)mentioning
confidence: 99%
“…Glucokinase is essential for glucose metabolism in the ␤ cell; some mutations in the glucokinase gene reduce the affinity of the enzyme for glucose resulting in a small increase in the plasma glucose concentrations (11). While this subtype accounts for 60% of MODY in France (12), it is less prevalent elsewhere (13,14). Recently, MODY3 was identified by linkage to a region on the long arm of chromosome 12 (15).…”
Section: Non-insulin-dependent Diabetes Mellitus (Niddm)mentioning
confidence: 99%
“…Linkage to MODY3 was found in 50% of the remaining nonglucokinase families (8), suggesting a prevalence of <25%. In contrast, glucokinase mutations are uncommon in U.K. MODY (11%) (13,14) and Japanese early onset NIDDM (0.5%) (15). It has been suggested that the difference between France and the U.K. reflects ascertainment differences resulting in a milder phenotype being more commonly collected in France (3,13).…”
mentioning
confidence: 99%
“…They code for the enzyme glucokinase (GGK/MODY2) (4) or for the transcription factors hepatocyte nuclear factor 4 alpha (HNF-4a/MODY1) (5), hepatocyte nuclear factor 1 alpha (HNF-1a/MODY3) (6), insulin promoter factor 1 (IPF1/MODY4) (7) and hepatocyte nuclear factor 1 beta (HNF-1b/MODY5) (8). The relative prevalences of the different subtypes of MODY have been shown to vary greatly in studies of British, French and German populations (9)(10)(11)(12)(13). MODY2 represents from 8 to 63% of cases (the most prevalent form in France) and MODY3 from 21 to 64% of cases (the most prevalent form in England).…”
Section: Introductionmentioning
confidence: 99%